2021
DOI: 10.32920/ryerson.14662683.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental Verification of Theoretical Ageing and Service Life Prediction Model for Vacuum Insulation Panels

Abstract: Vacuum Insulation Panels (VIPs) are a kind of the super-insulated materials (SIMs). VIPs are innovative material in various fields like the building sector as it encompasses a higher thermal resistance per unit of thickness compared to conventional insulation. To extensively use VIPs in the building sector, comprehensive performance analysis, and their properties such as thermal conductivity valuations are required to be done under simulated conditions to evaluate its longterm performance. However, different V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The thermal resistance for VIPs will decrease from air-and moisture entry into the panel and cause an increase in heat transfer by convection (air pressure) and conductivity (moisture content of core material) within the panel [67,16,72,73]. From experimental and numerical studies on the subject, it was found that for VIPs in cold climates it would require at least 20 years to double in thermal conductivity with proper moisture control [74,75,76,77,73]. The service life of the panels is dependent on the surrounding conditions, moisture control and the composition of the VIP barrier and core material.…”
Section: Enclosures With Low Conductivity Materialsmentioning
confidence: 99%
“…The thermal resistance for VIPs will decrease from air-and moisture entry into the panel and cause an increase in heat transfer by convection (air pressure) and conductivity (moisture content of core material) within the panel [67,16,72,73]. From experimental and numerical studies on the subject, it was found that for VIPs in cold climates it would require at least 20 years to double in thermal conductivity with proper moisture control [74,75,76,77,73]. The service life of the panels is dependent on the surrounding conditions, moisture control and the composition of the VIP barrier and core material.…”
Section: Enclosures With Low Conductivity Materialsmentioning
confidence: 99%